Pelatihan Soft Skill Untuk Meningkatkan Kualitas Dan Mutu Layanan Paud Di Desa Ngagel - Sumiyati Sumiyati (UIN Sultan Maulana Hasanuddin Banten, 2020)
This research is based on community service at the village of Ngagel, Dukuhseti District, Pati Regency. against the background of the education level of the Ngagel village community which is still low, and the quality of Early Childhood Education Institutions (PAUD) that are not in accordance with the principles of Early Childhood learning. Educators in early childhood education institutions in Ngagel village do not yet have an undergraduate education qualification, the majority are high school graduates. the teachers do not understand the ways to manage PAUD well, including not yet understanding how to make learning plans and prepare learning media that will be used in the learning process.Seeing this background, the community service program has a service program, especially in the field of education. This work program covers three main things namely; soft skills training, mentoring institutions and the formation of tutoring activities. All three of these programs is solution. Our soft skills training and institutional assistance is intended for teachers and institutions both PAUD and at the level of basic education, in order to improve the quality of learning at each level. while tutoring is intended for students from PAUD to high school. This program was quite successful with the full support of the local village government, namely the Ngagel village government along with the Ngagel village community leaders. Likewise, the high interest in learning from teachers and children in the village of Ngagel. Keywords: early childhood teachers; soft skills; Ngagel VillageReferencesAl-Abrasyi, M. A. (1996). Beberapa Pemikiran Pendidikan Islam. Jakarta: Titian Ilahi Press.Brewer, J. A. (2007). Introduction To Early Childhood Education. USA: Pearson Education, Inc.Depdiknas RI. (2002). Acuan Menu Pembelajaran pada Anak Usia Dini Usia (Menu Pembelajaran Generik). Jakarta: Depdiknas RI.Depdiknas RI. (2007). Penyelenggaraan PAUD. Jakarta: Depdiknas RI.Dirjend Dikti Depdiknas RI. (2007). Naskah Akademik Pendidikan Guru Pendidikan Anak Usia Dini (PG-PAUD) dan Rambu-rambu Penyelenggaraan Program S-1 Pendidikan Guru Pendidikan Anak Usia Dini (Program S-1 PG-PAUD). Jakarta.Djuwita, W., & Fakhri, M. (2019). Pengaruh Permainan Tradisional Dalam Mengembangkan Kecerdasan Jamak Anak Usia Dini Pada PAUD Di Kota Mataram. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(2), 87–102.Hasanah, H. (2018). Peningkatan Kemampuan Mengenal Lambang Huruf Melalui Metode Proyek Dan Media Bungkus Makanan Dan Minuman Ringan Pada Kelas B Di RA Riyadul Fata Tembongraja Kecamatan Salem Kabupaten Brebes. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 101–124. Hasbullah. (2016). Model Pengembangan Kurikulum PAUD. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 21–28. Hayati, N. R. (2016). Pendidikan Pra Sekolah (Pendidikan Anak Usia Dini) Dalam Islam. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 72–82. Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Imroatun, I. (2016). Bermain Sebagai Metode Pembelajaran Utama Anak Raudhatul Athfal. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 40–48. Mansur. (2007). Pendidikan Anak Usia Dini dalam Islam. Yogyakarta: Pustaka Pelajar.Musaropah, U. (2016). Pemberdayaan Masyarakat Dalam Penyelenggaraan Pendidikan Anak Usia Dini Berbasis Pesantren. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 177–185. Nuryati, N. (2016). Pengembangan Kompetensi Profesional Guru Pendidikan Anak Usia Dini Melalui Pemberdayaan Organisasi Himpaudi Di Kecamatan Serang. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 165–176. Nuryati, N. (2017). Perkembangan intelektual pada anak usia dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 59–78. Diambil dari http://jurnal.uinbanten.ac.id/index.php/assibyan/article/view/1346Pemerintah Desa. (2019). Data Desa Ngagel Kecamatan Dukuhseti Kabupaten Pati Jawa Tengah. Pati.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Santrock, J. W. (2007). Child Development (11 ed.). Jakarta: Erlangga.Setiani, R. E. (2019). Pemanfaatan Permainan Tradisional Dalam Penanaman Nilai-Nilai Kebangsaan Di Tk Negeri Pembina 2 Purwokerto. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 39–52. Sujiono, Y. N. (2007). Konsep Dasar Pendidikan: Anak Usia Dini. Jakarta: Universitas Negeri Jakarta.Ulwan, A. N. (n.d.). Pendidikan Anak Menurut Islam Pendidikan Sosial Anak. Bandung: Rosdakarya.Zuhri, S. (2017). Perkembangan Normatif Dan Non-Normatif Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 75–84.